Sharia Supervisory Board in Limited Company-Based Sharia Banks - Nurhasanah Nurhasanah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
This paper aims to examine the function of the Sharia Supervisory Board (SSB) due to the inconsistency of laws and regulations concerning this body. Law No. 21 of 2008 on Sharia Banking has required every Sharia Bank and Sharia Business Unit in the Banks to form an SSB. However, Law No. 40 of 2007 on Limited Liability Companies has not regulated the SSB as a corporate organ. This paper analyzes laws and regulations on the SSB and court decisions on cases resulting from legal inconsistencies, with the organizational structure and fiduciary duty theories as analytical frameworks. This study finds out that legal ambiguity results in the absence of coordination between the SSB and other bodies in the organization. Thus, this prevents the SSB from optimally carrying out its functions and roles. Among the consequences is the inability to ensure sharia compliance in business contracts leading to lawsuits to cancel the contracts.